2020
DOI: 10.1101/2020.08.04.20168112
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 in Niger State: A Pilot Cross Sectional Study

Abstract: Coronavirus Disease 2019 (COVID-19) Pandemic is ongoing, and to know how far the virus has spread in Niger State, Nigeria, a pilot study was carried out to determine the COVID-19 seroprevalence, patterns, dynamics, and risk factors in the state. A cross sectional study design and clustered-stratified-Random sampling strategy were used. COVID-19 IgG and IgM Rapid Test Kits (Colloidal gold immunochromatography lateral flow system) were used to determine the presence or absence of antibodies to SARS-CoV-2 in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 25 publications
(36 reference statements)
11
28
1
Order By: Relevance
“…The overall seroprevalence in the current study of 23.7% after the first wave is higher than in countries with a higher average income, lower inequality and an ability to shelter their population, such as Germany and Ireland [ 25 ]. However, our result is similar to a sample from a pilot study in Niger State, Nigeria (Gini index 0.35) which reported a seroprevalence of 25.4% independent of rural or urban residence [ 26 ], and to the studies which reported higher seroprevalences in more densely populated areas within countries. For example, the overall seroprevalence of a convenience sample from New York State in the USA was 12.5%, but in New York City itself, where population density and inequality between neighbourhoods is higher, the estimated cumulative incidence of COVID-19 cases was 22.7% [ 27 ].…”
Section: Discussionsupporting
confidence: 90%
“…The overall seroprevalence in the current study of 23.7% after the first wave is higher than in countries with a higher average income, lower inequality and an ability to shelter their population, such as Germany and Ireland [ 25 ]. However, our result is similar to a sample from a pilot study in Niger State, Nigeria (Gini index 0.35) which reported a seroprevalence of 25.4% independent of rural or urban residence [ 26 ], and to the studies which reported higher seroprevalences in more densely populated areas within countries. For example, the overall seroprevalence of a convenience sample from New York State in the USA was 12.5%, but in New York City itself, where population density and inequality between neighbourhoods is higher, the estimated cumulative incidence of COVID-19 cases was 22.7% [ 27 ].…”
Section: Discussionsupporting
confidence: 90%
“…The overall seroprevalence in the current study of 23.7% after the rst wave, is higher than in countries with high average income, low inequality and an ability to shelter their population, such as Germany and Ireland (22). However, our result is similar to a sample from a pilot study in Niger State, Nigeria (Gini index 0.35) which reported a seroprevalence of 25.4% independent of rural or urban residence (23), and to the studies which reported higher seroprevalences in more densely populated areas within countries. For example, the overall seroprevalence of a convenience sample from New York State in the USA was 12.5%, but in New York City itself, where population density and inequality between neighbourhoods is higher, the estimated cumulative incidence of COVID-19 cases was 22.7%.…”
Section: Discussionsupporting
confidence: 68%
“…Apart from these, another three studies had a sum of high and unclear risk of bias higher than the low risk of bias (16,20,27) the mean, median and SD were 2.62, 3.0 and 1.46, respectively. Considering each domain in all studies, >75% low risk of bias across the studies were observed in five domains.…”
Section: Resultsmentioning
confidence: 98%
“…Two studies showed overall unclear risk of bias ( 34,49 ). Apart from these, another three studies had a sum of high and unclear risk of bias higher than the low risk of bias ( 16,20,27 ) (Appendix 2, Figure). Considering the nine domains established and three possible answers (low, unclear, and high), on average 6.35, 1.43 and 1.19 of each option was chosen, respectively.…”
Section: Resultsmentioning
confidence: 99%